1992
DOI: 10.1039/ft9928800243
|View full text |Cite
|
Sign up to set email alerts
|

Role of metastable phases in the spontaneous precipitation of calcium carbonate

Abstract: This paper reports a study of the spontaneous precipitation of calcium carbonate from aqueous solutions which are very supersaturated with respect to calcite, both in the absence of inhibitors, and in the presence of triphosphate as inhibitor. The sequence of events during precipitation is governed strongly by the initial supersaturation, t h e temperature, and t h e presence or absence of triphosphate.At high supersaturation, the first-formed phase is an amorphous calcium carbonate. It is observed only above … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
208
2
4

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 250 publications
(231 citation statements)
references
References 20 publications
17
208
2
4
Order By: Relevance
“…The calculation methods are based on thermodynamic equilibria of all species in the solution, including the activity correction in or-der to approach their exact composition. More often than not, solubility calculations are only applied to calculate new dissociation constants [6][7][8][9][10] or initial solution compositions [11][12][13][14][15][16][17]. Thus, solubility calculations are only applied in general to equilibrated systems.…”
Section: Introductionmentioning
confidence: 99%
“…The calculation methods are based on thermodynamic equilibria of all species in the solution, including the activity correction in or-der to approach their exact composition. More often than not, solubility calculations are only applied to calculate new dissociation constants [6][7][8][9][10] or initial solution compositions [11][12][13][14][15][16][17]. Thus, solubility calculations are only applied in general to equilibrated systems.…”
Section: Introductionmentioning
confidence: 99%
“…ACC is highly unstable in vitro [11,12]. The discovery that echinoderm larvae form their skeleton through an amorphous precursor phase was followed by a series of studies which showed that echinoderm adults also adopt the same strategy [13], as do larval mollusks [14,15] and mature mollusks [16].…”
Section: Historical Perspectivementioning
confidence: 99%
“…There is a so-called "confusion principle" in glass physics that relates to this process [57]. It has been shown in vitro that Mg [58], phosphate [12] and silicate [59] stabilize ACC. It has also been shown that certain proteins that are extracted from calcium carbonate-containing mineralized tissues can stabilize ACC in vitro either transiently or permanently [17,25,60,61].…”
Section: Broader Implications Of a Transient Precursor Phase Strategymentioning
confidence: 99%
“…Calcium carbonate is highly polymorphic in that it can exist in six different crystal structures. The first polymorph formed after nucleation is often amorphous calcium carbonate (ACC), which subsequently crystallizes (6,7). ACC has no long-range order, but it often has short-range structural order that appears to determine the lattice structure after crystallization (8).…”
mentioning
confidence: 99%